SINGH’S PERSPECTIVE ON MULTISET THEORY - A CONSERVATIVE EXTENSION OF STANDARD SET THEORY - Peter, Chinedu; Abdullahi, Balarabe (FUDMA JOURNAL OF SCIENCES, 2025)
In this paper, we demonstrate that Singh’s approach to defining membership—through its novel yet underutilized notation—allows for a seamless and unambiguous analysis of multisets alongside their set counterparts. This stands in contrast to the widely used cardinality-based approach prevalent in existing literature. The Singh’s dressed epsilon approach () provides a membership-based way of handling multisets, in contrast to the cardinality-based approach that relies on counting functions (Cm(x)) or M(x)).